2019
DOI: 10.20869/auditf/2019/156/024
|View full text |Cite
|
Sign up to set email alerts
|

Financial Auditor Profession’s Attractiveness for Y Generation Millennials

Abstract: Today's students are part of Generation Y (Millennials) and have certain specific characteristics that employers cannot ignore when they enlarge their staff. The profile and expectations of this generation differ greatly from those of previous generations. In this regard, the research aims to question the undergraduate and master students that attend or have attended economic background Universities in Romania, in order to highlight the understanding and attractiveness of the profession of financial auditor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 19 publications
0
7
1
Order By: Relevance
“…It offers no support to accept the H3. Our study result deviates from the findings suggested by Tiron-Tudor et al (2019) that job insecurity and instability may not influence the intention to pursue accounting qualifications among the young Millennials.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…It offers no support to accept the H3. Our study result deviates from the findings suggested by Tiron-Tudor et al (2019) that job insecurity and instability may not influence the intention to pursue accounting qualifications among the young Millennials.…”
Section: Discussioncontrasting
confidence: 99%
“…The study outcome accords with the results suggested by Schoenfeld et al (2017) that perception of higher personal capabilities nurtures the inclination to engage in account qualification. Personal capacity and aptitude facilitate learning and promote the positive predispositions to engage in higher education or professional qualification ( Tiron-Tudor et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations